Bacillariophyceae Diversity as Bioindicator of Pollution in the Coastal Waters of Klui Beach, North Lombok - Yuni Safrian Hadi; Lalu Japa; Lalu Zulkifli (Jurnal Biologi Tropis, 2023)
Klui Beach is one of some famous beaches tourism destination in the Northern part of Lombok Island which is commonly visited by many tourists. Tourisms and resindents activities that take place around the coast can produce various wastes that have some prominent impact on pollution, for reducing water quality. Bacillariophyceae is a class of phytoplankton that is commonly abundant in marine waters and can be used as an indicator for controlling of water quality. The objectives of this study were to determine the level of pollution in the coastal waters of Klui Beach based on the Bacillariphyceae diversity index. The Haphazard sampling was applied for determining the sampling sites. The results showed that the composition species of Bacilllariophyceae consisted of 48 species which included in 17 orders. Average species abundance was 298.09 ind/L (low category). The spesies diversity index was 2.37 (moderate category). The level of water pollution in the Klui Beach was classified as not polluted.